Understanding the physiological responses to low nitrogen and molecular screening of selected rice genotypes for TOND1 gene - SB, Sujata; SNP, Nirakar; Batta, Bishal B; Nagireddy, Ranjit K; Sabarinathan, S; Subudhi, HN; Meher, J; Reddy, J N; A, Anandan (ORYZA-An International Journal of Rice, 2019)
Nitrogen (N) plays a major role in the growth and development of a plant. Extensive application of N fertilizers results in low N use efficiency (NUE) generated by N loss due to denitrification byammonia volatilization, surface runoff, and leaching in the soil-flood water system. Therefore, there is an urgent requirement for the development of rice varieties with high NUE, which may improve the yield and decrease the N application which is harmful to the environment. In the present study, variability and correlation of morpho-physiological traits among the rice genotypes under low N in hydroponic solution was carried out for further genotyping with Tolerance of Nitrogen Deficiency 1 TOND1 gene markers. The root parameters and traits associated with shoot growth observed from 30 days old rice seedlings under low N condition suggested that shoot length was positively associated with leaf and root number followed by root length. The genetic diversity was estimated among the 36 selected genotypes with TOND1 gene primers. A total of 14 alleles were identified with an average number of alleles of 2.33 per locus. Allele frequency ranged from 0.62 to 0.86 with an average of 0.76. Genetic Diversity index ranged from 0.23 to 0.46 with an average of 0.35. The observed heterozygosity ranged from 0.00 to 0.1429 with an average of 0.056. The PIC values ranged between 0.61 and 0.77 with an average of 0.69. The unweighted neighbour-joining dendrogram grouped the 36 genotypes into 3clusters, wherein the local land race IC517708 clustered with known N deficiency tolerant Tequing. Therefore, the identified N deficiency tolerant genotype may be used as donor in developing N use efficient cultivar.